Роль наративної компетентності в розвитку лідерських якостей - Романовський, Олександр Георгійович; Клочко, Софія Андріївна (Національний технічний університет "Харківський політехнічний інститут", 2024)
Статтю присвячено теоретичному огляді зв’язку наративної компетентності з лідерськими якостями. Проведено аналіз наукових досліджень, що дозволив визначити ключові елементи наративної компетентності майбутнього лідера. Розкрито зміст особливостей наративної компетентності в процесі підготовки майбутніх лідерів різних спеціальностей в умовах освітніх трансформацій. Наведено наративні практики, які можна використовувати з ціллю покращення якості лідерської діяльності. Висвітлено рекомендації стосовно поліпшення рівня наративної компетентності для перспективних лідерів та обґрунтовано пояснення подальшого дослідженнями у визначених областях наративу та лідерства.

The article is devoted to a theoretical review of the relationship between narrative competence and leadership qualities. In the context of improving national education, the problem of professional training of competent, competitive specialists remains particularly significant. The analysis of scientific research has made it possible to identify the key elements of the narrative competence of a future leader. The content of the features of narrative competence in the process of training future leaders of various specialties in the context of educational transformations is revealed. The narrative practices that can be used to improve the quality of leadership are presented. Recommendations for improving the level of narrative competence for prospective leaders are highlighted and the reasons why it is necessary to continue research in certain areas of narrative and leadership are substantiated.
The role of narrative competence in the development of leadership qualities
Keywords: наратив; наративна компетентність; лідерство; narrative; narrative competence; leadership